Productivity and profitability of organic and conventional potato (Solanum tuberosumL.) production in West-Central Bhutan - Norden Lepcha; Panya Mankeb; Suneeporn Suwanmaneepong (Open Agriculture, 2021)
Abstract Bhutan aspires to be an entirely organic nation. Food self-sufficiency and increasing farm household income are critical priorities in the country. Realising these priorities necessitates assessing the country’s current organic agriculture performance. The objectives of this study were to investigate the productivity and profitability of organic and conventional potato and farmers’ constraints in producing organic potato in West-Central Bhutan. Multistage and purposive sampling techniques were used to select the study sample. A semi-structured questionnaire and face-to-face interviews were employed to gather primary data for the 2019 cropping cycle from 93 potato farmers: 43 organic farmers in the Gasa District and 50 conventional farmers in Wangdue Phodrang District. Descriptive statistics, cost and return analysis, and independent sample t -test were applied for data analysis. The results revealed that the conventional potato’s productivity (tuber yield) and profitability were significantly higher ( p < 0.001) than organic potatoes. The average productivities for organic and conventional potatoes were 7.48 and 19.22 t/ha, respectively. Organic potato farmers incurred a loss of −202,708.47 Ngultrum (Nu)/ha, while conventional potato farmers incurred a profit of 83,832.85 Nu/ha. The benefit-cost ratios of organic and conventional potato stood at 0.40 and 1.27, respectively. Lack of premium price, pest and disease problems, low crop productivity, and climate change were the constraints faced by organic potato farmers. The study found that the productivity and profitability of the conventional potatoes were higher than the organic potatoes in West-Central Bhutan in the current scenario. Further, the critical information will contribute to guiding Bhutan’s vision for its organic agriculture development.
Keywords: Agricultural Economics and Policy